LITERATURE STUDY: APPLICATION OF DIFFERENTIATION LEARNING IN IMPROVING LITERACY AND NUMERACY OF ELEMENTARY SCHOOL STUDENTS - Nissa, Khoirrun; Darmawan, Puguh (Publikasi dan UKI Press UKI Toraja., 2024)
Basic education serves as a crucial foundation in individual and societal development. Within the context of the independent curriculum, literacy and numeracy emerge as primary focuses. Enhancing literacy and numeracy stands as a key to providing a sturdy groundwork for individual development. However, results from PISA indicate that literacy and numeracy achievements in Indonesia still require improvement. Differentiated learning emerges as an effective strategy in enhancing students' literacy and numeracy skills by considering the needs and diversity of learners. Research findings demonstrate that differentiated learning can enhance student activity, learning outcomes, motivation, and inclusivity within the classroom. Statistical analyses further corroborate the effectiveness of differentiated learning in enhancing student capabilities. Therefore, differentiated learning warrants implementation as part of efforts to enhance educational quality at the primary school level.